The first thousand years of glass-making in the ancient Near East compositional analyses of late Bronze and Iron Age glasses. - READE, WENDY (Archaeopress archaeology., 2021)
This volume explores glass composition and production from the mid-second to mid-first millennia BC, the first thousand years of glass-making. Multi-element analyses of 132 glasses from Pella in Jordan, and Nuzi and Nimrud in Iraq (ancient Mesopotamia) produce new and important data that provide insights into the earliest glass production.